Is Adolescent Risk Behavior Associated With Cross-Household Family Complexity? An Analysis of Post-separation Families in 42 Countries - Schnettler, Sebastian; Steinbach, Anja (Frontiers in Sociology, 2022)
We examine whether complex cross-household structures of post-separation families are associated with higher risk-taking behavior in adolescence (substance use, bullying, early sexual onset) and whether the proportion, and thus statistical normality, of complex family types in a certain country is a potential moderator of this association. Drawing on representative data from 42 countries and regions from the Health Behavior in School-aged Children (HBSC) study in 2001, 2006, and 2010 (N = 506,977), we provide detailed analyses on adolescent risk behavior even for very rare family types, thereby accounting for the complex cross-household structure present in many post-separation families. We combine logistic and count regression models to analyze risk incidence and intensity. Controlling for relevant child and family characteristics, our results reveal a gradient along which adolescent risk-taking increases with family complexity: The incidence and intensity of risk-taking among adolescents is lowest in two-biological-parent and highest in two-household families with stepparents in both households. The association decreases with a higher proportion of the respective family type in a country. However, the differences between family types, other than the two-biological parent family, are not as pronounced as expected.